Ultrasound Detection of Regional Oxidative Stress in Deep Tissues Using Novel Enzyme Loaded Nanoparticles. Issue 5 (12th January 2017) - Olson, Emilia S.; Ortac, Inanc; Malone, Christopher; Esener, Sadik; Mattrey, Robert
Abstract : Oxidative stress is a powerful tool that is critical to immune mediated responses in healthy individuals, yet additionally plays a crucial role in development of cancer, inflammatory pathologies, and tissue ischemia. Despite this, there remain relatively few molecular tools to study oxidative stress, particularly in living mammals. To develop an intravenously injectable probe capable of labeling sites of oxidative stress in vivo, 200 nm catalase synthetic hollow enzyme loaded nanospheres (catSHELS) are designed and fabricated using a versatile enzyme nanoencapsulation method. catSHELS catalyze H2 O2 to water and oxygen producing microbubbles that can be detected and imaged using a clinical ultrasound system. catSHELS are optimized in vitro to maximize ultrasound signal and their functionality is demonstrated in rat ischemic renal injury model. Ischemic oxidative injury is induced in a single kidney of normal rats by clamping the renal artery for 1 h followed by 2 h of reperfusion. Imaging of both kidneys is performed following the intravenous bolus injection of 10 12 catSHELS of the optimized formulation. There is significant increase in ultrasound signal of the injured kidney relative to controls. This method offers a novel intravenous approach to detect oxidative stress in deep tissues in living animals. Abstract : 200 nm catalase synthetic hollow enzyme loaded nanospheres (catSHELS) are intravenously injectable probes capable of labeling sites of oxidative stress in vivo. catSHELS catalyze H2 O2 to water and oxygen producing microbubbles that can be detected and imaged using a clinical ultrasound system. The functionality of catSHELS is demonstrated in rat ischemic renal injury model in vivo.